“I FINISHED COLLEGE DURING THE PANDEMIC”: IN THE WORDS OF GRADUATES OF THE BUSINESS ADMINISTRATION COURSE AT A BRAZILIAN PUBLIC UNIVERSITY - Vital, Mirian Serrão (Seven Editora, 2025)
The objective of this study was to analyze the perceptions of graduates of the Administration Program at the Amazonas State University (UEA), Brazil, regarding remote classes during the COVID-19 pandemic. The qualitative approach, using interviews, emphasized aspects related to Emergency Remote Learning (ERE) and the teaching-learning process. The sample included eight graduates who completed the program during the pandemic. The data were processed through content analysis, and the main results, regarding ERE, indicated that most graduates had good internet service and adequate and comfortable spaces to attend classes. Efficient time management presented a challenge. Regarding the teaching-learning process, it was emphasized that it was average and did not negatively impact academic development. Finally, in times of crisis and remote classes, activities that offer greater integration between students and teachers should be valued, as they enhance the teaching-learning process.DOI: https://doi.org/10.56238/sevened2025.030-008